The relationship between IFNL4 genotype and the rate of fibrosis in hepatitis C patients. (2nd September 2019) - Shridhar Gulati, Rachna; Wimalanathan, Thakshani; Norheim Andersen, Solveig; Isaksen, Kjetil; Lagging, Martin; Midgard, Håvard; Moghaddam, Amir; Dalgard, Olav
Abstract: Introduction: IFNL4 rs12979860 genotype CC is associated with increased ALT activity and liver stiffness in hepatitis C virus (HCV) genotype (G) 3 infection but not in G1. The primary aim of this study is to assess an interaction between IFNL4 genotype, viral genotype and the stage of liver fibrosis. Secondary aims are to study the potential interactions between IFNL4 genotype, viral genotype and viral load as well as ALT levels. Methods: We performed a cross sectional study of patients with untreated chronic hepatitis C. Inflammation and liver fibrosis were scored using METAVIR. DNA was extracted from serum samples and the rs12979860 was genotyped using a custom made Taqman assay. Results: About 304 consecutive patients with chronic Hepatitis C were included. 52% had G1 infection and 48% had G3. Among patients with G3, advanced fibrosis or cirrhosis (F3F4) was present in 35% of the patients with IFNL4 CC and 28% with CT/TT ( p = 0.24). Among patients with G1, F3F4 was present in 20% of the patients with IFNL4 CC and 19% with CT/TT ( p = 0.52). IFNL4 CC was associated with higher mean value of normalized (n)ALT both in HCV G1 and G3 infection. Conclusions: IFNL4 genotype was not a predictor of advanced liver fibrosis in G3 or G1 infected patients. IFNL4 CC predicted a higher mean value of ALT among both G1 and G3 infected patients.